2019
DOI: 10.1177/1094428119872531
|View full text |Cite
|
Sign up to set email alerts
|

How Are We Testing Interactions in Latent Variable Models? Surging Forward or Fighting Shy?

Abstract: Latent variable models and interaction effects have both been common in the organizational sciences for some time. Methods for incorporating interactions into latent variable models have existed since at least Kenny and Judd, and a great many articles and books have developed these methods further. In the present article, we present an empirical review of the methods that organizational science investigators use to test their interaction hypotheses. We show that it is very common for investigators to use fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 154 publications
(125 reference statements)
2
43
0
Order By: Relevance
“…Specifically, when researchers test relationships among reflective constructs that do not involve interactions using latent factor models and in the interaction testing step ignore the reflective measurement model of the moderator, they send an inconsistent message about the theoretical assumptions to the reader. Our call to hospitality researchers is consistent with pleas in other business areas, such as organizational behavior, where researchers equally welcome latent models as long as they do not test for interaction effects (Cortina et al, 2020). We advise hospitality researchers to branch out beyond the inherited construct operationalizations and statistical traditions and practice uniformity in selected procedures.…”
Section: Discussionsupporting
confidence: 58%
“…Specifically, when researchers test relationships among reflective constructs that do not involve interactions using latent factor models and in the interaction testing step ignore the reflective measurement model of the moderator, they send an inconsistent message about the theoretical assumptions to the reader. Our call to hospitality researchers is consistent with pleas in other business areas, such as organizational behavior, where researchers equally welcome latent models as long as they do not test for interaction effects (Cortina et al, 2020). We advise hospitality researchers to branch out beyond the inherited construct operationalizations and statistical traditions and practice uniformity in selected procedures.…”
Section: Discussionsupporting
confidence: 58%
“…Recent research has shown that correcting for measurement error is particularly critical when dealing with interaction terms—as required to specify a moderating effect in, for example, conditional process models (Li et al, 2019). The reason is that the attenuating effect of measurement error is exacerbated in the product of two error-prone measures (Cortina et al, 2020). For instance, when a predictor and moderator are uncorrelated, the reliability of the interaction term is the product of the predictor’s and moderator’s reliabilities (Aguinis et al, 2017; Busemeyer & Jones, 1983).…”
Section: Process Versus Pls-semmentioning
confidence: 99%
“…A common objection regarding the use of SEM for estimating conditional process models is that the estimation of interaction terms is far from trivial, and its specification is still subject to debate in the methodological literature (e.g., Cortina et al, 2001, 2020; Sardeshmukh & Vandenberg, 2017). Commenting on these issues, Hayes et al (2017) note that “it can be difficult to trust a model which involves estimating latent variable interactions because it is difficult to determine whether the resulting estimates of interactions are reasonable” (p. 80).…”
Section: Process Versus Pls-semmentioning
confidence: 99%
See 1 more Smart Citation
“…The latent moderation variable was produced using the semTools package (Jorgensen et al, 2019) using match-paired approach (Marsh, Wen, & Hau, 2004) and double-mean centring for the product of the indicators (Lin, Wen, Marsh, & Lin, 2010). When testing the moderation effects of variables that are not directly observed, the measurement error should be accounted, as such, latent variable moderation should be preferred (Cortina, Markell-Goldstein, Green, & Chang, 2019;Sarstedt, Hair, Nitzl, Ringle, & Howard, 2020). The idea that measurement error can be ignored consists of what Edwards (2009) classified as one "of the seven deadly myths of testing moderation" (p. 143).…”
Section: Discussionmentioning
confidence: 99%